(untitled) (Journal of Universal Science Research, 2023)
X-ray crystallography is an empirical scientific method used to elucidate the arrangement of atoms and molecules within a crystal. When an incident beam of X-rays encounters a crystal, its crystalline structure causes the X-rays to diffract into specific directions. By measuring the angles and intensities of these diffracted beams, a crystallographer can generate a three-dimensional representation of the electron density within the crystal. From this electron density map, valuable information can be derived, including the average positions of atoms within the crystal, their chemical bonds, the degree of disorder in the crystal lattice, and various other structural characteristics. X-ray crystallography serves as a powerful tool for understanding the internal structure and properties of crystalline materials.